First-trimester maternal renin-angiotensin-aldosterone system activation and the association with maternal telomere length after natural and IVF/ICSI conceived pregnancies: the Rotterdam periconception cohort - D. Aoulad Fares; R.E. Wiegel; A.J. Eggink; J.B.J. van Meurs; S.P. Willemsen; A.H.J. Danser; R.P.M. Steegers-Theunissen (Taylor & Francis Group, 2023)
Objective To study associations between the first-trimester maternal determinants of renin-angiotensin-aldosterone system (RAAS) activation and telomere length (TL) in pregnancies conceived natural and after IVF/ICSI. Methods In 145 pregnancies of the Rotterdam Periconception cohort renin, prorenin and aldosterone concentrations were measured in maternal blood at 9 weeks gestational age (GA). TL was measured by qPCR at 20 weeks GA. Results A significantly negative correlation was found between renin and TL, which was attenuated for prorenin but not observed for aldosterone. Maternal TL was significantly shorter in pregnancies conceived after in-vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) compared to natural pregnancies. Conclusion The negative association between first-trimester maternal renin and maternal TL, and the shorter maternal TL in women after IVF/ICSI treatment compared to natural pregnancies, substantiates the role of excessive RAAS activation.